Nanoscale Bonding between Human Bone and Titanium Surfaces: Osseohybridization. (15th January 2015) - Kim, Jun-Sik; Kang, Seok-Man; Seo, Kyung-Won; Nahm, Kyung-Yen; Chung, Kyu-Rhim; Kim, Seong-Hun; Ahn, Jae-Pyeong
Abstract : Until now, the chemical bonding between titanium and bone has been examined only through a few mechanical detachment tests. Therefore, in this study, a sandblasted and acid-etched titanium mini-implant was removed from a human patient after 2 months of placement in order to identify the chemical integration mechanism for nanoscale osseointegration of titanium implants. To prepare a transmission electron microscopy (TEM) specimen, the natural state was preserved as much as possible by cryofixation and scanning electron microscope/focused ion beam (SEM-FIB) milling without any chemical treatment. High-resolution TEM (HRTEM), energy dispersive X-ray spectroscopy (EDS), and scanning TEM (STEM)/electron energy loss spectroscopic analysis (EELS) were used to investigate the chemical composition and structure at the interface between the titanium and bone tissue. HRTEM and EDS data showed evidence of crystalline hydroxyapatite and intermixing of bone with the oxide layer of the implant. The STEM/EELS experiment provided particularly interesting results: carbon existed in polysaccharides, calcium and phosphorus existed as tricalcium phosphate (TCP), and titanium existed as oxidized titanium. In addition, the oxygen energy loss near edge structures (ELNESs) showed a possibility of the presence of CaTiO3 . These STEM/EELS results can be explained by structures either with or without a chemical reaction layer. The possible existence of the osseohybridization area and the form of the carbon suggest that reconsideration of the standard definition of osseointegration is necessary.